Patterns of hepatic resections in North America: use of concurrent partial resections and ablations. Issue 10 (October 2016) - Gani, Faiz; Thompson, Vanessa M.; Bentrem, David J.; Hall, Bruce L.; Pitt, Henry A.; Pawlik, Timothy M.
Abstract: Background: National registries have not adequately captured concurrent partial hepatic resections or ablations. Therefore, the aim of this analysis was to describe the patterns of concurrent partial resections and ablations in North America. Methods: Patients undergoing a hepatic resection were identified using the American College of Surgeons-National Surgical Quality Improvement Program Targeted Hepatectomy database. Perioperative outcomes were compared for patients undergoing concurrent "wedge" resections and/or ablations and other subsets. Results: A total of 2714 patients were identified who met inclusion criteria. Major hepatectomy was performed in 1037 patients (38.2%) while partial lobectomy was performed in 1677 (61.8%) patients. Concurrent "wedge" hepatic resections and ablations were undertaken in 56.0% and 14.2% of patients, respectively, and were more frequently performed among patients undergoing a partial lobectomy and among patients undergoing surgery for colorectal liver metastasis (both p < 0.001). While associated with a decreased incidence of postoperative complications (p = 0.027) and liver failure (p = 0.031) among patients undergoing a major hepatectomy, concurrent therapies were associated with comparable 30-day outcomes for patients undergoing partial lobectomy. Conclusion: Concurrent "wedge" hepatic resections and ablations are performed in 56.0% and 14.2%, respectively of patients undergoing hepatectomy. Concurrent procedures were not associated with worse clinical outcomes.